Prophetic Leadership in Pesantren Education: Study at Pondok Pesantren Universitas Islam Indonesia - Hamid, Noor; Juliansyahzen, Muhammad Iqbal (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
This paper discusses prophetic leadership in Islamic educational institutions of Pondok Pesantren Islamic University of Indonesia (PP UII). Prophetic leadership is a strategic offer in the discourse of Islamic leadership. There are three basic principles of prophetic leadership: humanization, liberation, and transcendence. These three principles are internalized in the leadership patterns applied by the leaders at Pondok Pesantren Islamic University of Indonesia (PP UII). Leadership in PP UII is different from pesantren in general. If the pesantren generally put forward the leadership of charismatic, while the leadership in PP UII put forward the style of legal leadership. The legal authorities make it more necessary to work together systemically in realizing the vision and mission of the establishment of pesantren. Leadership in pesantren with a periodization system allows for a different concept of understanding of the vision and mission of pesantren between one leader and his successor. Thus, the system and the blueprint of leadership must be clear and mature so that whoever leads the establishment of pesantren remains well done